EFEKTIVITAS KERJASAMA WWF INDONESIA – BBSKDA RIAU DALAM MEMERANGI PERDAGANGAN ILEGAL GADING GAJAH SUMATERA DI PROVINSI RIAU 2010-2015 - Philippe Bangun; Ika Riswanti Putranti; Marten Hanura (International Relations, Faculty of Social and Political Sciences, Universitas Diponegoro, 2017)
Illegal ivory trade crime is an environmental issue that threatens the elephant’s population in the world, one of them is Sumatran elephant. In Riau Province, the Centre of Sumatran Elephant Conservation, illegal ivory trade still took place and often conducted by riding the human – elephant conflict that was one of the main threats of Sumatran Elephant’s population. Relatively easy access to Southeast Asian’s country from Riau Province has led the crime to be classified as transnational crime because of its impact to other countries. Responding the issue, WWF Indonesia established a cooperation with BBKSDA Riau in an effort of Sumatran elephant conservation in 2010 and extended in 2015. The goal of this research is to know how effective is WWF Indonesia and BBKSDA Riau’s cooperation on combating illegal Sumatran elephant ivory trade in Riau Province in 2010-2015. In order to answer that question, this research uses concepts that are: International Organization, International Cooperation, Environmental Crime and Effectiveness. The method that being used in this research is mixed methods with descriptive type by using data collecting technique which are interview, literature reviews and questionnaire. The result from this research is that the effectiveness of WWF Indonesia – BBKSDA Riau cooperation on combating illegal Sumatran elephant ivory trade in Riau Province in 2010-2015 is less effective due to its lack of significance towards addressing the issue.